Contemporary migration literature in German and English: a comparative study (Colloquia Comparativa Litterarum, 2025)
Sandra Vlasta. Contemporary Migration Literature in German and English: A Comparative Study. (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, vol. 187). Leiden/Boston, Brill /Rodopi, 2015, 296 p.